Role of nonperturbative field configurations in phase transitions - Carvalho, C. Arago de; Éboli, O. J.P.; Marques, G. C. (American Physical Soc, 1986)
We analyze the importance of nonperturbative field configurations for phase transitions in field theory at finite temperatures. We show, by analyzing different approaches used to investigate this problem, that some of these field configurations play indeed an essential role in the phase transition. The different schemes to determine the temperature for which this happens lead to exactly the same result. © 1986 The American Physical Society.